2017
DOI: 10.1097/opx.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Correlational Study of Diabetic Retinopathy and Hearing Loss

Abstract: When adjusted to include diabetes control, the severity of diabetic retinopathy showed a correlation with degree of hearing loss at most levels. Because of this association, recommendation for hearing evaluations may be considered for those with mild, moderate, or severe nonproliferative or proliferative diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
4
21
0
Order By: Relevance
“…The analysis showed that the condition was significantly associated with age, male gender, consanguinity, family history of DM, and elevated blood pressure. More recently from a study by Ooley et al [ 9 ] after controlling for glucose control, as measured by HbA1c and renal function measured with serum creatinine, the presence of diabetic retinopathy was significantly associated with the severity of hearing loss in both ears (right ear, P = .018 and left ear, P = .007). Usually, the chronic hyperglycemia in diabetic patients could affect hearing leading to hearing impairment.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The analysis showed that the condition was significantly associated with age, male gender, consanguinity, family history of DM, and elevated blood pressure. More recently from a study by Ooley et al [ 9 ] after controlling for glucose control, as measured by HbA1c and renal function measured with serum creatinine, the presence of diabetic retinopathy was significantly associated with the severity of hearing loss in both ears (right ear, P = .018 and left ear, P = .007). Usually, the chronic hyperglycemia in diabetic patients could affect hearing leading to hearing impairment.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study have revealed high prevalence of hearing impairment in association with retinopathy in T2DM patients. The association between diabetes and eye disease is well recognized with diabetic retinopathy as the most common eye disease in subjects with T2DM [ 9 ]. However, the link between diabetes and hearing loss has not been universally accepted until recently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data have shown that the incidence of diabetic cataracts in both types of diabetes is close to 15%. Given the increase in diabetes prevalence and the duration of the disease, this figure is likely to rise ( 9 ). The progression of diabetic cataracts is fast and poses a serious threat for blindness among advanced diabetic patients.…”
Section: Discussionmentioning
confidence: 99%